The application of the 'fabric first' approach to improve thermal comfort and energy efficiency in affordable housing in Southern Brazil - Camboim Salatino Tubelo, Renata (2016)
In 2009 the Brazilian government committed to support the construction of nearly 24 million new dwellings by 2022 through its housing programme Minha Casa, Minha Vida (My House, My Life). The initiative aims to tackle the housing shortfall of 5.546 million residential units and the 10.948 million units that are considered inadequate dwellings with poor living conditions. The potential economic, social and environmental impact of such large initiative is vast and consequently it is essential that the new dwellings are planned, designed and built to meet high levels of energy efficiency and thermal comfort.